The Rational Sequence Topology Is Partially Metrizable - Assaf, Samer; Cuchta, Tom (Topology Proceedings, 2023)
In this paper, the rational sequence topology is shown to be partially metrizable. This shows that, contrary to a previously stated conjecture, it is possible to have a non-metrizable Tychonoff partial metric space. Furthermore, new conjectures pertaining to the topological structure of partial metric spaces and their possible metrizability are stated.